Relevansi Mediasi Penal di Indonesia dalam Perspektif Pembaharuan Hukum Pidana - Prayoga, I Wayan Didik; Setiabudi, I Ketut Rai (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 4 (2021), 2021)
This study aims to describe and analyze the concepts of restorative justice and penal mediation which are linked to their existence and relevance to their application in the Indonesian criminal justice system in the perspective of criminal law reform. The research method used is a normative legal research method with the approach used is the statue approach, the concept approach, and the comparative approach. The results of this study, firstly, penal mediation is one form of the implementation of restorative justice which views crime as not only an act that violates the law, but more broadly as an act that violates the balance in society. Second, penal mediation is relevant to be applied in the Indonesian criminal justice system in the future, especially from the perspective of the urgency of criminal law reform, and to answer the problems faced by the Indonesian criminal justice system. Penelitian ini bertujuan untuk mendeskripsikan serta menganalisis paradigma keadilan restoratif dan mediasi penal yang dikaitkan eksistensinya dan relevansi penerapanya dalam sistem peradilan pidana Indonesia dalam perspektif pembaharuan hukum pidana. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan yang digunakan adalah pendekatan perundang-undangan (statue approach), dan pendekatan konsep (conceptual approach). Hasil dari penelitian ini, pertama mediasi penal merupakan bagian dari pelaksanaan keadilan restoratif yang memandang kejahatan tidak hanya perbuatan yang melanggar undang-undang, melainkan lebih luas sebagai perbuatan yang melanggar keseimbangan dalam masyarakat. Kedua, mediasi penal relevan untuk diterapkan dalam sistem peradilan pidana Indonesia di masa depan khususnya ditinjau dari perspetif urgensi pembaharuan hukum pidana, dan untuk menjawab persoalan yang dihadapi sistem peradilan pidana Indonesia.